Geographical variations of elytral color polymorphism in Cheilomenes sexmaculata (Fabricius) (Coleoptera: Coccinellidae). Issue 2 (16th January 2013) - Kawakami, Yasuko; Yamazaki, Kazuo; Ohashi, Kazunori
Abstract: The geographical variation in elytral color polymorphism in Cheilomenes sexmaculata (Fabricius) was analyzed based on data from specimen surveys. In all, 1549 individuals collected from different latitudes throughout Indonesia to Japan were categorized into 20 morph types of elytra. Results show that the morph types have a geographical cline: dark types increased with latitude, although the light types showed higher relative frequency in lower latitudes, which suggests that the geographic variation in elytral color polymorphism in C . sexmaculata is a product of selection by climate. The darker morph types might be advantageously able to make fuller use of insolation at higher latitudes, whereas the lighter morph types were likely to reduce heat stress at lower latitudes. In most areas across Southeast and South Asia, all specimens were of the lightest type, which may imply either: (i) the saturation of genes expressing light morph types, which have less solar absorption, due to tropical climate; or (ii) an enhanced warning function of bright red against predators. On Miyako Island of Japan, a unique frequency of morph types was found compared to the adjacent areas.